Daedalus Mega-ichnosites: The Armorican Quartzite Bridge between Villuercas-Ibores-Jara and Naturtejo UNESCO Global Geoparks - Carlos Neto de Carvalho; Andrea Baucon; Ivan Cortijo; Soren Jensen; Jose Maria Barrera; Javier Lopez Caballero (Geoconservation Research)
The Early Paleozoic oceans were generally characterized by short trophic chains and simple ecological tiering dominated by suspension-feeding organisms. However, the Great Ordovician Biodiversification Event (GOBE) was responsible for the complexification of food webs, increasing depth and diversity of substrate ecospace utilization and increasing benthic competition for resources near the water-substrate interface. Daedalus is an enigmatic trace fossil that precedes this period of nearshore innovation and its disappearance is probably related to the escalation in tiering complexity, especially among benthic surficial feeders, that may have cut access to their main food sources. Daedalus producers were responsible for the occupation of some of the earliest deep substrate tiers, probably feeding from particulate organics and meiofauna using complex architectures for resource exploitation. They were responsible for characteristic ichnofabrics that can be found, especially in Lower-to-Middle Ordovician sandstones, in the “Armorican Quartzite” and similar nearshore facies around Gondwana. Villuercas-Ibores-Jara and Naturtejo UNESCO Global Geopark show several geosites where the best-preserved forms of Daedalus can be found and where its crowded ichnofabrics can be followed in large-scale exposures. Indeed, these are mega-ichnosites of international paleontological relevance for understanding behavior and ecospace utilization of a characteristic trace fossil during the GOBE. This paleoecological significance meant that Daedalus became a symbol for a cross-border Interreg Project that connects the two UNESCO geoparks. The Armorican Quartzite Route is an 800 km-long road following the main geological structures and promoting sustainable tourism attractions along the way. The Bridge over the Armorican Quartzite has the goal of fostering sustainable development through common scientific and education tools, raising awareness of the GOBE as one of the most important events of biodiversification in the Earth history and a key element of the geological heritage of both UNESCO Geoparks.